Basic aspects of methodology for justifying the performance characteristics of a tracked machine with electromechanical transmission - V. N. Kuznetsova; R. V. Romanenko (Вестник СибАДИ, 2020)
Introduction. High rates of new territories development, the development of the construction and road-transport complex, mining and transportation of minerals is impossible without machinery and equipment. The use of a caterpillar propeller as a base chassis has both advantages and disadvantages. One of the main problems is ensuring the mobility of tracked vehicles. The use of mixed-type power units and transmissions allows solving this scientific problem and ensuring the efficiency of technological operations during the operation of tracked vehicles. Modern vehicles use a variety of transmission types, including electromechanical transmission (EMT). In such a design, torque conversion and change in the speed of the drive wheels of the caterpillar propulsion device are carried out by means of traction electric motors (TEM). The aim of the use of electromechanical transmission in tracked machines is to increase the tractive-dynamic properties and fuel economy and, as a result, to improve the mobility of the machine. The combination of an internal combustion engine (ICE) and electric machines in a caterpillar machine (CM) makes it possible to maximize the advantages of the latter and compensate for the disadvantages of each. These improvements are achieved mainly through the different performance characteristics of the traction electric engine (TEE) and the energy storage device (ESD).Research methods. A system analysis served as the basis for the theoretical studies. A mathematical model of the motion of a tracked vehicle with an electromechanical transmission has been developed. The methods of the theory of algorithms were used.Results. A structural diagram of the arrangement of a series connection of elements of an electromechanical transmission of a tracked vehicle, protected by a patent of the Russian Federation, has been developed and presented. An algorithm has been developed for the interaction of its elements taking into account the movement of the machine. The main mathematical relationships included in the methodology for substantiating the operational characteristics of a tracked vehicle with an electromechanical transmission are presented.Discussion and conclusion. Using the developed approaches and methodology, it will be possible to calculate the components of the electromechanical transmission in order to ensure the required mobility of the caterpillar machine, to assess its fuel economy, as well as its maximum and average speed.